2007
DOI: 10.5380/avs.v12i3.10927
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização Sorológica Dos Antígenos De Superfície Em Cepas De Escherichia Coli Isoladas De Suínos Com Diarréia No Estado Do Paraná

Abstract: O presente trabalho teve como objetivoa caracterização sorológica de 42 cepas deEscherichia coli isoladas no Centro de DiagnósticoMarcos Enrietti em Curitiba, PR de surtos de diarréiasuína no Estado do Paraná. Os antígenos desuperfície O-K e de aderência foram identificadosno Centro de Pesquisas Veterinárias Desidério Finamor(RS), e na UNICAMP (SP), respectivamente.Os principais sorogrupos mais prevalentes foramO138:K81 e O141:K85, ocorrendo na mesmaproporção, em 9 (21,4%) cepas; O139:K82 em 4(9,5%) e O149:K91… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…An F4 vaccine was able to protect piglets that received antibodies through colostrum during weaning (NAGY & FEKETE, 1999). A study conducted with samples from a diarrhea outbreak in the Paraná state of Brazil found a 52% prevalence of F4 in the analyzed samples (SOUZA et al, 2007).…”
Section: Etiologymentioning
confidence: 99%
“…An F4 vaccine was able to protect piglets that received antibodies through colostrum during weaning (NAGY & FEKETE, 1999). A study conducted with samples from a diarrhea outbreak in the Paraná state of Brazil found a 52% prevalence of F4 in the analyzed samples (SOUZA et al, 2007).…”
Section: Etiologymentioning
confidence: 99%